Effect of lithium citrate on hydration of cement paste. (15th July 2022) - Ben, Xunqin; Jiang, Linhua; Guo, Ming-Zhi; Jin, Weizhun; Chen, Lei; Zhi, Fanfan; Gao, Song; Xia, Kailun
Abstract: This paper systematically investigated the influence of lithium citrate on the properties of cement. Its effect on hydration heat and internal pore structures was examined by isothermal calorimeter and mercury intrusion porosimetry (MIP) analysis, respectively. The evolution of hydration products and changes of the ion concentration in the pore solution were also investigated by thermal gravimetric (TG), X-ray diffraction (XRD)and Inductively Coupled Plasma (ICP). Thermodynamic model was used to further reveal the relationship between lithium citrate and hydration products. The results showed that lithium citrate first retarded the cement hydration, but improved the strength subsequently functioning as an accelerator as early as 7 curing days. This was because upon the addition in the cement, lithium citrate immediately formed a protective outer layer wrapping around cement clinker particles. As hydration further proceeded, the protective layers were gradually broken down, and the released lithium ions then promoted the hydration of C3 A to form a lithium aluminate amorphous gel compound, providing new sites for cement hydration and contributing to a higher content of portlandite and calcite, which in turn augmented the strength. Highlights: The effect of lithium citrate on early properties of cement paste was studied. The mechanism of lithium citrate on cement paste was described. The thermodynamic model was employed to analyze the relationship between the lithium citrate and the hydration products.